New record of the genus Probethylus Ashmead, 1902 (Hymenoptera: Sclerogibbidae) for Argentina - Saint Esteven, Alejandro (2022)
Sclerogibbid wasps conform a small group of chrysidoids and parasitoids of embiopterans especially found in arid and semiarid habitats. Although its distribution in America is fairly well known, information about sclerogibbid wasps from Argentina is scarce. The first record of a species belonging to the family Sclerogibbidae (Hymenoptera) for the province of San Juan, Argentina is reported. It is a female individual collected by pitfall trap in the Multiple Use Reserve of Valle Fértil and identified as Probethylus callani Richards, 1939. This new and atypical record encourages to expand the taxonomic research in the region, given that Valle Fértil was characterized as an area of high prevalence of endemisms.